Análisis de Peligros Basados en la Inocuidad de Embutido no Cocidos que se expenden en la Ciudad de Babahoyo - Paredes Cerezo, Jonathan David (2024)
This literature review examined the physical, chemical and biological hazards associated with the production of raw sausages, as well as the preventive and corrective measures proposed by the respective authors. Regarding physical hazards, the importance of preventing the presence of foreign objects in raw materials, which can seriously endanger the health of consumers and the reputation of the company, was highlighted. In addition, the need to maintain machines in good condition and train personnel to use them properly to avoid damage and ensure the quality of the final product was emphasized. Regarding chemical hazards, it emphasizes the importance of the proper use of chemical products such as pesticides, herbicides and cleaning agents to avoid contamination of raw sausages. It also warns against the excessive or incorrect use of preservatives such as nitrates and nitrites, which can be harmful to health and must be carefully controlled. Finally, as regards biological hazards, the need to prevent contamination by pathogenic microorganisms such as Salmonella, Listeria monocytogenes and E. coli was highlighted, as well as the risk of growth of bacteria such as Clostridium botulinum in inadequate packaging conditions. Measures such as the implementation of a microbial quality control system, strict personal and equipment hygiene and temperature control during storage and transport are recommended.